2002
DOI: 10.1542/peds.110.4.720
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Health Maintenance Organization Hospitalist System in Academic Pediatrics

Abstract: A pediatric hospitalist system within a staff-model HMO significantly improved LOS, cost, and parental ratings of care without affecting rates of posthospitalization follow-up. Additional studies are needed both to measure broader aspects of quality and to assess the impact of such a program on patients being cared for through other types of delivery and insurance systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 21 publications
2
50
0
Order By: Relevance
“…23,31 The mortality in children without critical illness admitted to general pediatric wards is significantly lower. 30 In agreement with the increasing rate of obesity among children with diabetes, 32,33 especially in minority populations, we found that hospitalized children with a history of diabetes and glucose >180 mg/dL had a higher body mass index than those with normoglycemia (P < .001). Obesity in children has been associated with the presence of several comorbidities and an increased risk of hospital complications.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…23,31 The mortality in children without critical illness admitted to general pediatric wards is significantly lower. 30 In agreement with the increasing rate of obesity among children with diabetes, 32,33 especially in minority populations, we found that hospitalized children with a history of diabetes and glucose >180 mg/dL had a higher body mass index than those with normoglycemia (P < .001). Obesity in children has been associated with the presence of several comorbidities and an increased risk of hospital complications.…”
Section: Discussionsupporting
confidence: 79%
“…This is in contrast to our previous results in adult patients, in whom inpatient hyperglycemia was found to represent an important marker of increased morbidity and mortality among both those critically ill and not critically ill. 3 It is important to note that the overall mortality rate reported in children with hyperglycemia relates to severity of illness and is significantly lower than that of adults. 30 In most critically ill pediatric series, hospital mortality ranges from 2% to 5.3% and is higher in patients with severe trauma and those who underwent major cardiac surgery. 23,31 The mortality in children without critical illness admitted to general pediatric wards is significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Death is a rare occurrence in pediatric ward settings, and the seven studies conducted to date comparing pediatric hospitalist and traditional systems have been universally underpowered to detect differences in mortality. 9,[12][13][14][15][16][17][18] There is a need to better understand care processes as a first step in understanding and improving quality of care in hospitalist systems. 19 The Pediatric Research in Inpatient Settings (PRIS) Network was formed to improve the quality of care for hospitalized children through collaborative clinical research.…”
Section: Design and Measurementsmentioning
confidence: 99%
“…Bellet and Whitaker, 13 Landrigan et al, 14 Ogershok et al, 16 and Bekmezian et al 18 reported reductions in cost for all patients varying from 9% to 29%, while Wells et al 15 and Srivastava et al 17 found reductions in cost only for patients with certain diagnoses. Srivastava et al 17 analyzed 1970 patients, admitted with primary diagnoses of asthma, dehydration, or viral illness, over a 5-year period from 1993 to 1997.…”
Section: No Difference In Readmission Ratesmentioning
confidence: 99%
“…The studies by Dwight et al, 12 Bellet and Whitaker, 13 Landrigan et al, 14 Ogershok et al, 16 Bekmezian et al, 18 and Boyd et al 21 examined mortality and readmission rate. None of these studies reported differences in mortality rate, though none were powered to do so.…”
Section: Other Quality Measuresmentioning
confidence: 99%